Selective sorting of semiconducting single-walled carbon nanotubes using thienylenevinylene-based conjugated polymers with high alkyl side-chain density. (December 2017) - Lee, Min-Hye; Lee, Seung-Hoon; Kim, Jihong; Lee, Sol Yi; Lim, Dae-Hee; Hwang, Kyoungtae; Hwang, Hansu; Jung, Yong Chae; Noh, Yong-Young; Kim, Dong-Yu
Abstract: The demand for high-purity semiconducting single-walled carbon nanotubes (sc-SWNTs) has increased considerably with the aim of utilizing their superior properties in a range of future applications. Among post-sorting methods, conjugated polymers have been regarded as one of the candidates to selectively isolate sc-SWNTs with uniform electrical properties. Herein, we demonstrate the ability to selectively sort two types of SWNTs by the two polymers PCTV18T and PC12TV18T, which have different alkyl side-chain densities. PC12TV18T, with a high alkyl chain density, shows great sorting ability for both high-pressure carbon monoxide and plasma-torch-grown SWNTs with a weight ratio of almost 1:1 in toluene solution. In addition, it is found that PC12TV18T selectively sorts sc-SWNTs with the high purity. The chirality and diameters of the enriched sc-SWNTs are further confirmed by Raman spectroscopy and photoluminescence excitation/emission mapping. Finally, we fabricate bottom gate/bottom contact thin-film transistors using the enriched sc-SWNTs as semiconductors to verify the electrical performance. Devices with well-percolated sc-SWNT networks displayed p -dominant properties with average charge-carrier mobilities of 2.05 cm 2 V −1 S −1 and 9.87 cm 2 V −1 S −1 and on/off current ratios of approximately 10 4 and 10 5 for high-pressure carbon monoxide and plasma-torch-grown SWNTs, respectively. Graphical abstract: